Examining the phenomenon of rounding in analysts’ EPS forecasts: Evidence from Singapore - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2021)
Prior studies have documented the phenomenon of rounding of analysts' earnings per share (EPS) forecasts in the USA. From the outset, it is unclear if analysts following Singapore firms also similarly engage in the rounding of their EPS forecasts. This study aims to investigate the extent to which analysts engage in rounding of EPS forecasts of firms listed on the Singapore Exchange.